1996
DOI: 10.1021/jp953538d
|View full text |Cite
|
Sign up to set email alerts
|

Supercooled Liquids and Glasses

Abstract: Selected aspects of recent progress in the study of supercooled liquids and glasses are presented in this review. As an introduction for nonspecialists, several basic features of the dynamics and thermodynamics of supercooled liquids and glasses are described. Among these are nonexponential relaxation functions, non-Arrhenius temperature dependences, and the Kauzmann temperature. Various theoretical models which attempt to explain these basic features are presented next. These models are conveniently categoriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

59
1,778
2
13

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 2,050 publications
(1,892 citation statements)
references
References 120 publications
59
1,778
2
13
Order By: Relevance
“…So, according to the fragility scale the PMMA network can be classified as a kinetically fragile system with a non-Arrhenius transport behaviour. As expected for fragile systems the apparent activation energy is high, usually fragile systems have E a of 500 kJ/mol or more near T g (in our case E a is even higher), corresponding to a change in dynamics of one decade for a temperature change of 3-5 K [3].…”
Section: Fragilitysupporting
confidence: 67%
See 2 more Smart Citations
“…So, according to the fragility scale the PMMA network can be classified as a kinetically fragile system with a non-Arrhenius transport behaviour. As expected for fragile systems the apparent activation energy is high, usually fragile systems have E a of 500 kJ/mol or more near T g (in our case E a is even higher), corresponding to a change in dynamics of one decade for a temperature change of 3-5 K [3].…”
Section: Fragilitysupporting
confidence: 67%
“…Many liquids (including covalent, ionic and metallic) are able to solidify into a disordered glassy structure upon cooling below their melting point, if crystallisation is prevented [1][2][3]. The glass transition corresponds to the freezing of the liquid-like mobility at the length scale of several molecular units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no doubt that the time scale for relaxation increases dramatically (faster than an Arrhenius law for what are called "fragile" glasses) as the temperature is lowered from the melt towards the glass transition temperature, T g , but it is much less clear whether there are any static growing length scales that can be identified that accompany the slowing down [128,129]. However, as is well-documented in this book, there is a growing length scale associated with heterogeneities in the dynamics, which become increasingly collective as the viscosity increases.…”
Section: Connection With Super-cooled Liquidsmentioning
confidence: 99%
“…DOI: 10.1103/PhysRevLett.99.135701 PACS numbers: 64.70.Pf, 61.43.Fs, 82.70.Dd The underlying reasons for the dramatic increase in the viscosity of glass-forming liquids are not well understood. It has become increasingly clear that simple structural measures remain short-ranged close to the glass transition, and thus a growing simple static length scale does not appear to be implicated [1]. This has led to the search for a growing dynamical length scale that drives vitrification.…”
mentioning
confidence: 99%